2015
DOI: 10.4038/jas.v10i3.8067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blanching on antioxidant, nutritional and physical properties of bamboo shoot

Abstract: Quality of bamboo shoots gets deteriorate rapidly during storage and transportation due to enzymatic browning and microbial attack. Therefore, effect of blanching temperature (75, 85 and 95°C) and time (5, 10, 15, 20, 25 and 30 min) on different physic-chemical properties of bamboo shoot cubes were assessed. Blanching time and temperature have significantly influenced the nutrients like protein, carbohydrate and reducing sugar contents. The highest changed in values of protein, carbohydrate and reducing sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The crude fat content was almost in-line with those as reported by Bhatt et al [36]. Badwaik et al [32] observed that temperature and duration of blanching treatment significantly (P < 0.05) affected crude fat content. Blanching for 30 min resulted in the reduction of crude fat from 0.52 g/100g to 0.38, 0.28 and 0.19 g/100g at 75 °C, 85…”
Section: Processing Effect On Proximate Parameterssupporting
confidence: 88%
“…The crude fat content was almost in-line with those as reported by Bhatt et al [36]. Badwaik et al [32] observed that temperature and duration of blanching treatment significantly (P < 0.05) affected crude fat content. Blanching for 30 min resulted in the reduction of crude fat from 0.52 g/100g to 0.38, 0.28 and 0.19 g/100g at 75 °C, 85…”
Section: Processing Effect On Proximate Parameterssupporting
confidence: 88%
“…Uyan et al (2004) reported antioxidant capacity of purple carrots was reduced after blanching in water at 98°C for 2 min (Uyan et al, 2004). Antioxidant and phenolics content of all vegetables except for cabbage and mustard cabbage was reduced after 5-10 min blanching in hot water at 98°C (Badwaik et al, 2015;Ismail and Lee, 2005). The antioxidant activity was increased by 9%, 40%, 4%, and 19% in mustard cabbage, Chinese cabbage, red cabbage, and Chinese white cabbage, respectively, after 15 min of blanching.…”
Section: Blanchingmentioning
confidence: 97%
“…According to Badwik et al [32], the maximum loss of phenolic content (from 101.65 mg/100 g to 39.34 mg/100 g) at 95 o C for 30 minutes blanching and the highest retention of phenolic content (from 101.65 mg/100 g to 59.57 mg/100 g) at 75 o C for 5 minutes blanching. High intensity heat treatment leads to the maximum loss of phenolic content, which may be due to thermal degradation, leaching or diffusion of component into water [33].…”
Section: Total Phenolics Total Flavonoids Content and Antioxidant Amentioning
confidence: 99%